Conceptualizing Activation Policies Targeted at Single Mothers: A Case Study of Australia and the United Kingdom. (7th June 2019) - Brady, Michelle
Abstract: Single parents are increasingly a target group for "activation" through new obligations to seek paid work or engage in education or training. Researchers commonly characterize new activation policies in terms of epochal shifts or unidirectional movements away from understanding single parents as "carers" or "mothers". This characterization downplays the degree to which the postwar welfare state viewed single parents as potential workers and the degree to which contemporary reforms view them as carers. Based on historical research and drawing on Foucault's concept of problematization and research on neoliberal governmentalities, pre-emptive politics and anticipatory modes of power, this article seeks to extend existing characterizations of activation policies for single parents.